2009
DOI: 10.1002/pi.2579
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the simultaneous effect of nano‐silica reinforcement and electron‐beam irradiation on a model LDPE/EVA‐based TPE system

Abstract: BACKGROUND: The technical properties of polyolefinic thermoplastic elastomer (TPE) systems can be modified significantly using fillers like nano-silica. Controlled irradiation can potentially be an effective way of tailoring the technical properties of such nano-silica-filled TPE systems. RESULTS: The effect of controlled electron-beam irradiation on the properties of a pristine silica nanoparticle-filled model low-density polyethylene/ethylene-(vinyl acetate) (LDPE/EVA) TPE system is explored in this paper. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Because of the higher atomic number of silica particles, radiation crosslinked interfacial area (also to some extent to the continuous matrix) is accordingly more. 15 Thus, initially viscosity is high. But after a certain shear rate, structural breakdown of EVA domains with aggregated silica particles occurs.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Because of the higher atomic number of silica particles, radiation crosslinked interfacial area (also to some extent to the continuous matrix) is accordingly more. 15 Thus, initially viscosity is high. But after a certain shear rate, structural breakdown of EVA domains with aggregated silica particles occurs.…”
Section: Resultsmentioning
confidence: 98%
“…4,7 In our system, silica particles play dual functions, namely, as reinforcing filler 12 and as radiation sensitizer. 15 In all the compositions, EVA domains have been found to exist as dispersed phase in the continuous matrix. 17 However, it has been found that in CS/3-1, in the continuous phase, due to intermixing of EVA and LDPE silica particles remained associated in both phases as well as in the interface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations